Dampak Coaching Pada Perubahan Diri dan Pekerjaan Pada Peserta Coaching di BPRS Buana Mitra Perwira Purbalingga - Prasetyo, Mokhammad Nur Fannie (Komunitas Manajemen Kompetitif, 2021)
This study aims to measure the impact of coaching on changes in self and work. The research method is to conduct a coaching session with the coachee and then ask qualitative feedback questions after the coachee completes the session. As a result, coaching has an impact on new awareness, changes in mindset, mental quality and then behavior. After that it affects work, results and or performance. The term coaching for performance is true, but it doesn't directly affect it. Because of its influence on the coachee first, then it will affect the coachee's work. So Coaching has an impact on self and work..